Институциональный менеджмент как инструмент управления организацией в условиях инновационно-институциональной экономики (Путеводитель предпринимателя, 2020)
The article identifies trends and dynamics of the formation of the innovation economy, the specifics of development organizations. On the basis of comparative analysis of the different going near theoretical description of structural components of organization the system structure of space of organization, consisting of the hierarchically associate fields, is exposed. Features and methods of management the resource field, field of knowledges and mental field of organization are exposed. Essence of institutional management and his role is formulated in a management organization in the conditions of innovative economy.